Advances in the thin-layer chromatographic forensic analysis of inks. Issue 12 (20th July 2016) - Sherma, Joseph
ABSTRACT: Advances in the use of thin layer and high-performance thin-layer chromatography for analysis of inks and ink writings in forensic investigations are reviewed. Experimental materials and techniques such as sample preparation, layers, sample application, development, detection, documentation, and interpretation of results are described and selected applications for several ink types are given. Some additional analytical techniques that complement thin-layer chromatography are also mentioned. Citations to important literature, from 2008 to 2016, are included. GRAPHICAL ABSTRACT: